Instructional Tasks for Fostering Scientific Creativity in Physics Education: A Systematic Review (2020–2024) - Saefan, Joko; Kurniawan, Wawan; Rini, Nur Widya (Lontar Physics Today, 2025)
This systematic literature review explores research on scientific creativity in physics education published between 2020 and 2024, with a particular focus on the intersection of instructional tasks and physics topics. Using PRISMA-based identification, screening, eligibility, and synthesis procedures, 130 initial records from Scopus were narrowed to 20 eligible studies that explicitly addressed both instructional task types and physics-related content. Instructional tasks were classified into seven categories as problem finding, open-ended problem solving, creative experiment design, hypothesis generation, modeling tasks, product improvement, and interdisciplinary tasks, while physics topics were coded from domain-specific subjects to broader categories. Findings indicate a strong dominance of modeling tasks, particularly when paired with general topics, reflecting their adaptability to varied instructional contexts and alignment with STEM or STEAM frameworks. In contrast, tasks such as creative experiment design and product improvement were less represented, and domain-specific topics appeared infrequently. This pattern suggests a tendency toward flexible but generalized approaches to fostering creativity, potentially at the expense of deep disciplinary engagement. The review highlights the need to diversify instructional tasks and embed creative learning within core physics content. These insights carry implications for curriculum design, teacher professional development, and future research aiming to balance interdisciplinary breadth with disciplinary depth in promoting scientific creativity in physics education.